2021
DOI: 10.1111/rda.13955
|View full text |Cite
|
Sign up to set email alerts
|

Sperm subpopulations influence the pregnancy rates in cattle

Abstract: This study aimed to study the characteristics and subpopulations of spermatozoa from bulls with low and high reproductive performance based on pregnancy rates.Based on historical records of pregnancy rate from four farms, 24 bulls were selected. Two groups were established, with low pregnancy rates (n = 12; LOW), including bulls that presented pregnancy rates <52.27% (33.33% to 51.81%); and a group with high pregnancy rates (n = 12; HIGH), with pregnancy rates >52.27% (52.27% to 69.64%), after fixed-time artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In our work, we found subpopulations characterized by the presence of trajectories sinuous (Subpopulations 2 and 4) and nonlinear. This is in line with the fact that more significant percentages of fast and nonlinear sperm seem to have greater fertilization capacity [27].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our work, we found subpopulations characterized by the presence of trajectories sinuous (Subpopulations 2 and 4) and nonlinear. This is in line with the fact that more significant percentages of fast and nonlinear sperm seem to have greater fertilization capacity [27].…”
Section: Discussionsupporting
confidence: 79%
“…The statistical management of the data impacts on the prediction of fertility. For instance, in bulls' subpopulation analysis associated with the clustering method can be considered effective tin predicting higher fertility [27]. However, in boars, the clustering of the ejaculates using the means per ejaculate of all kinematic variables has a limited predictive capacity for litter size and fertility variables [28].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a relationship between the sperm subpopulation with rapid progressive swimming pattern and in vitro fertility has been found for frozen–thawed spermatozoa from Holstein bulls [ 38 ] and dogs [ 23 ]. The importance of fast-moving sperm cells for fertility was also supported by Hidalgo et al (2021); however, this study reported the rapid non-progressive sperm cells to be correlated with the fertility outcome [ 39 ].…”
Section: Discussionmentioning
confidence: 75%
“…According to Hidalgo et al (2021), an excellent progressive percentage in bull fertility is 39.33%. The progressive of frozen semen for Limousin bulls aged 3, 8, and 12 years showed good results because it exceeded the standard value.…”
Section: Discussionmentioning
confidence: 99%